Gastrointestinal Tuberculosis after Vedolizumab Treatment in Inflammatory Bowel Disease: Brief Report - Sharma, Vishal; Nagarajan, Kayal Vizhi; Pathak, Parna; Agarwal, Rishabh; Patil, Nikhil; Vaiphei, Kim; Bhat, Naresh (Journal of Gastrointestinal Infections, 2024)
Vedolizumab is a humanized anti-α4β7 integrin monoclonal antibody used to treat patients with moderate to severe inflammatory bowel disease who are refractory or intolerant to conventional therapy. It has an excellent safety profile in terms of the risk of serious or opportunistic infections primarily due to its gut-selective action. The reported risk of tuberculosis after vedolizumab treatment is considered very low. We report two cases of gastrointestinal tuberculosis in patients on vedolizumab who were tested negative for latent tuberculosis infection screening.
Keywords: microbiology; pathology; endoscopy; tuberculosis; vedolizumab